(untitled) (Bangladesh Journal of Neuroscience, 2016)
Background: The diagnosis of ischemic stroke remains a clinical one, with confirmatory evidence obtained through neuroimaging. Analogous to the role that the creatine kinase (CK), a biochemical test may be useful in diagnosis as well as detect severity which ultimately helps in the management of acute ischemic stroke. Objective: To evaluate serum creatine kinase level and its association with severity in acute ischemic stroke patients. Methods: This cross-sectional analytic study was carried out in the Department of Neurology, BSMMU, Dhaka from January 2014 to December 2014.In this study 50 acute ischemic stroke patients were enrolled as cases. Result: In this study, 42.0% patients were female and 58% were male and their mean age was 55.96±10.93 years. According to classification by NIH Stroke score, 32% patients was found in minor stroke, 28% in moderate stroke, 26% in moderate to severe stroke and 14% in severe stroke. 80.0% patients had increased level of serum creatine kinase. In this study there is a positive correlation between NIH Stroke Score and Serum creatine kinase level (r= 0.869, p < 0.0001). Conclusion: Increase severity of acute ischaemic stroke causes increased level of serum creatine kinase. Bangladesh Journal of Neuroscience 2016; Vol. 32 (2): 52-55